Analisis Perkembangan Kreativitas Anak melalui Permainan Tradisional: Stimulasi Kreativitas Anak Usia SD melalui Permainan Tradisional - Sudarjat Sudarjat; Adhy Putri Rilianti (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2022)
Creativity is one of the characteristics of children's growth and development in the cognitive realm. Creativity is very important to be developed from an early age because this ability is a provision to solve problems in everyday life. One way to improve and develop children's creativity is to play traditional games. This study aims to explore information about stimulating children's creativity through traditional games. This research is in the form of a literature review with secondary sources in the form of books, journals, and other relevant sources. The results showed that traditional games that can stimulate children's creativity include 1) gobag sodor, 2) congklak, and 3) painting.